PREVALENCE AND DETERMINANT FACTORS OF NEONATAL SEPSIS AMONG NEONATES ADMITTED AT HIWOT-FANA SPECIALIZED REFERRAL HOSPITAL, HARAR, ETHIOPIA, 2020: Neonatal Sepsis - Arif Hussen Jamie (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Neonatal sepsis is a systemic infection occurring in neonatal life and is a major cause of morbidity and mortality in newborns .It accounts for five million newborn deaths  Objectives:- The objective of this study was to assess Prevalence of neonatal sepsis and its determinant factors among neonates admitted in Hiwot-Fana Specialized Referral Hospital, Harar, Ethiopia, 2020 Methods: An institution based cross-sectional study with retrospective document review method was conducted in Hiwot-Fana Specialized Referral Hospital in Harar town. Sample size was calculated by using single population proportion sample formula and the final sample size was 292.The study subject was selected by using systematic random sampling method, and adopted data collection tool was used. Data was analyzed by using SPSS version-20. Descriptive analyses were performed and bivariate analyses were used to find out the association of independent variables. Result: The overall prevalence of neonatal sepsis in this study was 52.7%..This study found out that PROM of the mother, gestational age of neonates and birth weight of the neonate were significantly associated with neonatal sepsis.. Conclusion: The associated risk factors for neonatal sepsis were identified as PROM of the mother, gestational age of neonates and birth weight of the neonate. Recommendation:Therefore, preventive efforts should focus on high risk neonates such as neonates born from mothers who have PROM, neonate with low birth weight and neonates born prematurely. Thus, a careful monitoring and follow up as well as rigorous treatment are needed.